Assessment of Human Epineural Conduit of Different Size Diameters on Efficacy of Nerve Regeneration and Functional Outcomes - Strojny, Marcin Michal; Kozlowska, Katarzyna; Brodowska, Sonia; Różczka, Klaudia; Siemionow, Maria (Journal of Reconstructive Microsurgery, 2022)
Background Different types of nerve conduits are used to bridge peripheral nerve gaps when a tension-free repair is unattainable. To best support nerve regeneration, naturally occurring conduits have been tested. Since allografts offer an unlimited source of epineurium, we have developed human epineural conduit (hEC) as a novel technology to bridge nerve gaps. Considering acellular properties, and lack of immunogenic response, epineurium-derived conduits represent an attractive material, when compared with nerve allografts that require systemic immunosuppression. In this study, we introduce the hEC as a novel naturally occurring material applied for repair of nerve gaps after trauma.Methods We tested the application of hEC created from human sciatic nerve in the restoration of 20 mm sciatic nerve defects in the nude rat model. Four experimental groups were studied: group 1: no repair control (n = 6), group 2: autograft control (n = 6), group 3: matched diameter hEC (n = 6), and group 4: large diameter hEC (n = 6). Functional tests of toe-spread and pin prick were performed at 1, 3, 6, 9, 12 weeks after repair. At 12 weeks, nerve samples were collected for immunostaining of Laminin B, S-100, glial fibrillary acidic protein (GFAP), nerve growth factor (NGF), vascular endothelial growth factor (VEGF), von Willebrand factor, and histomorphometric analysis of myelin thickness, axonal density, fiber diameter, and percentage of the myelinated nerve fibers. Muscle samples were gathered for gastrocnemius muscle index (GMI) and muscle fiber area ratio measurements.Results Best functional recovery, as well as GMI, was revealed for the autograft group, and was comparable to the matched hEC group. Significant differences were revealed between matched and large hEC groups in expression of S100 (p = 0.0423), NGF (p = 0.269), VEGF (p = 0.0003) as well as in percentage of myelinated fibers (p < 0.001) and axonal density (p = 0.0003).Conclusion We established the feasibility of hEC creation. The innovative method introduces an alternative technique to autograft repair of nerve defects.
Keywords: nerve gap repair; human epineural conduit; allograft; nerve regeneration; conduit of different size diameters